Pengaruh Perbandingan Kulit Biji Kakao (Theobroma cacao) dan Daun Mint (Mentha piperita L.) Terhadap Karakteristik Teh Herbal - Purba, Melini Pazyanita; Permana, I Dewa Gde Mayun; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i02.p06, 2024)
The processing of chocolate produces waste in the form of unused cocoa bean shells that can be used for making tea products. Astringent from theobromine compounds can be covered by adding the mint leaves that have menthol compound and can give a minty and fresh effect to the product. The research has been done to determine the effect of cocoa bean shells and mint leaves on herbal tea characteristics and find the best comparison of cocoa bean shells and mint leaves in producing the best characteristics of herbal tea. The analysis used a randomized group design with 5 comparison treatments of cocoa bean shells and mint leaves as follows: 100%:0%; 80%:20%; 60%:40%; 40%:60%; 20%:80%, with 3 repetitions to obtain 15 experimental units. The data was analyzed with ANOVA and if the treatment had a significant effect, then followed by a test of Duncan's Multiple Range Test (DMRT) at a 5% significant level. Parameters of this research observed moisture content, extract content, theobromine content, tannin content, antioxidant activity, and sensory evaluation consisting of color, taste, aroma, and overall acceptance with the hedonic test, and taste scoring test for taste. The comparison of cocoa bean shells and mint leaves affected the herbal tea characteristics. The best comparison with sensory criteria showed that herbal tea with 40% cocoa bean shells and 60% mint leaves was the best treatment with moisture content (7.03%), extract content (10.15%), total flavonoid content (18.80 mgQE/g), theobromine content (2.04%), tannin content (11.90 mgTAE/g), antioxidant activity (28.56%), color was liked, the taste was slightly astringent and slightly liked, aroma slightly liked, and overall acceptance slightly liked.